Novel peptides that inhibit heparanase activation of the coagulation system - Axelman, Elena; Henig, Israel; Crispel, Yonatan; Attias, Judith; Li, Jin-Ping; Brenner, Benjamin; Vlodavsky, Israel; Nadir, Yona (Thrombosis and Haemostasis, 2014)
Heparanase is implicated in cell invasion, tumour metastasis and angiogenesis. It forms a complex and enhances the activity of the blood coagulation initiator – tissue factor (TF). We describe new peptides derived from the solvent accessible surface of TF pathway inhibitor 2 (TFPI-2) that inhibit the heparanase procoagulant activity. Peptides were evaluated in vitro by measuring activated coagulation factor X levels and co-immunoprecipitation. Heparanase protein and/or lipopolysaccharide (LPS) were injected intra-peritoneally and inhibitory peptides were injected subcutaneously in mouse models. Plasma was analysed by ELISA for thrombin-antithrombin complex (TAT), D-dimer as markers of coagulation activation, and interleukin 6 as marker of sepsis severity. Peptides 5, 6, 7, 21 and 22, at the length of 11–14 amino acids, inhibited heparanase procoagulant activity but did not affect TF activity. Injection of newly identified peptides 5, 6 and 7 significantly decreased or abolished TAT plasma levels when heparanase or LPS were pre-injected, and inhibited clot formation in an inferior vena cava thrombosis model. To conclude, the solvent accessible surface of TFPI-2 first Kunitz domain is involved in TF/heparanase complex inhibition. The newly identified peptides potentially attenuate activation of the coagulation system induced by heparanase or LPS without predisposing to significant bleeding tendency.
Keywords: Heparanase; tissue factor; TFPI-2; peptides; anticoagulant